Metakognisi dan Theory of Mind (ToM) - Murti, Heru Astikasari Setya (Jurnal Psikologi: PITUTUR, 2011)
This  article  is  a  literature  review  on  the relationship  between  Metacognition  and Theory of Mind (ToM). Metacognition refers to the superordinat concept consisting of at least two  components,  namely  (1)  knowledge,  (2) monitoring (experience) and regulation (skills), and  often  refers  to  the  procedural metacognition,  while  ToM  can  be  defined  as knowledge about the existence and contents of the mind (eg beliefs, desires and intentions) as well as the ability to use the knowledge to make predictions and explanations of human action. Research on metacognition and ToM showed that the research data provided some evidence that  early  competence  of  ToM  can  be considered  as  the  precursor  of  metamemori and  the  acquisition  of  representations  of  the concept  is  probably  something  crucial  in  the development of children, which in turn enables them to think about their memory and others.